Employment Insurance reduces the impact of unemployment on food security - Li, Tim; Tarasuk, Valerie (My University, 2024)
Food insecurity, uncertain or inadequate access to food due to financial constraints, is a function of income adequacy and stability. To determine the impact of job loss on food insecurity, researchers compared households with similar sociodemographic characteristics but that differed in terms of whether the workers were continuously employed throughout the year. To determine the impact of Employment Insurance (EI), they compared households with workers who received EI and similar households with workers who did not receive EI. The findings contribute to a growing body of research showing that public programs reduce the risk of food insecurity when they improve households’ financial circumstances.
Keywords: Government; Income, pensions, spending & wealth; Labour